An investigation into the relationship of flexibility, power, and strength to club head speed in male golfers - Gordon, B. S.; Moir, G. L.; Davis, S. E.; Witmer, C. A.; Cummings, D. M. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this study was to investigate the relationship of flexibility, power, and strength to club head speed (CHS) in male golfers. Fifteen golfers (mean age ± SD: 34.3 ± 13.6 years) with a handicap of ?8 volunteered for the study. Following a standardized warm-up, subjects proceeded to hit 5 wiffle golf balls with a 5 iron while their CHS was measured. Rotational trunk flexibility was measured on a trunk rotator machine. An index of total body rotational power was measured through a hip toss with a 3-kg medicine ball while an 8-repetition maximum (RM) on a pec deck machine was used to measure chest strength. Pearson correlations were used to assess the magnitude of the relationships between CHS and the measures of flexibility, power, and strength. Partial correlations were then run to assess the effect of handicap on the observed relationships. The only variables that were significantly correlated to CHS were chest strength (r = 0.69, p < 0.05) and total body rotational power (r = 0.54, p < 0.05). These relationships were unchanged when the effect of handicap was controlled for. The results of this study show that strength of the chest in the pec deck motion and total body rotational power significantly correlate with CHS in male golfers. This information can be used by practitioners to develop training programs and field tests for golfers.